Interspecific differences in root exudation for three tropical seagrasses and sediment pore-water dissolved organic carbon beneath them. (December 2021) - Li, Linglan; Jiang, Zhijian; Wu, Yunchao; He, Jialu; Fang, Yang; Lin, Jizhen; Liu, Songlin; Huang, Xiaoping
Abstract: Seagrass beds act as blue carbon sinks globally; however, little attention has been given to carbon dynamics in the seagrass rhizosphere. Hence, in this study, the quantity and characteristics of dissolved organic carbon (DOC) from root exudation of the three dominant tropical seagrasses ( Thalassia hemprichii, Enhalus acoroides, and Cymodocea rotundata ) and sediment pore water beneath them were compared, to examine their interspecific differences, and to establish a connection between seagrass root exudation and sediment carbon. The rate of root-exuded DOC from T. hemprichii (2.15 ± 1.06 mg g DW root -1  h -1 ) was significantly higher (p < 0.05) than that from E. acoroides (0.72 ± 0.39 mg g DW root -1  h -1 ) and C. rotundata (0.46 ± 0.25 mg g DW root -1  h -1 ). Root exudation rates were more affected by root hair density and root hair length than by root carbon, nitrogen, and soluble sugar content. Simultaneously, DOC concentrations of the sediment pore water beneath T. hemprichii, E. acoroides and C. rotundata were 22.05 ± 11.61 mg l -1, 15.55 ± 2. 66 mg l -1, and 14.32 ± 1.82 mg l -1, respectively. The corresponding absorption coefficients at 254 nm (a254 ) were 30.53 ± 18.00, 17.31 ± 2.24, and 14.07 ± 2.03, respectively, while the relevant specific ultraviolet absorbances at 254 nm (SUVA254 ) were 1.38 ± 0.29, 1.19 ± 0.26 and 1.03 ± 0.28, respectively. Therefore, the roots of T. hemprichii exuded DOC at a higher rate, leading to a higher pore-water DOC pool in the sediment. This suggests that T. hemprichii played a greater role in the sediment carbon pool through root exudation. Thus, it can be considered as the priority species for transplantation to promote the carbon sink function of seagrass beds. Graphical abstract: Unlabelled Image Highlights: Interspecific differences in root exudation existed among three tropical seagrasses. Higher rate of root-exuded DOC from Thalassia hemprichii was observed. T. hemprichii played a greater role in sediment carbon pool through root exudation. T. hemprichii can be the priority species for transplantation to promote carbon sink.